Concise Review: Mending a Broken Heart: The Evolution of Biological Therapeutics. (16th March 2017) - Chen, Caressa; Termglinchan, Vittavat; Karakikes, Ioannis
Abstract : Heart failure (HF), a common sequela of cardiovascular diseases, remains a staggering clinical problem, associated with high rates of morbidity and mortality worldwide. Advances in pharmacological, interventional, and operative management have improved patient care, but these interventions are insufficient to halt the progression of HF, particularly the end-stage irreversible loss of functional cardiomyocytes. Innovative therapies that could prevent HF progression and improve the function of the failing heart are urgently needed. Following successful preclinical studies, two main strategies have emerged as potential solutions: cardiac gene therapy and cardiac regeneration through stem and precursor cell transplantation. Many potential gene- and cell-based therapies have entered into clinical studies, intending to ameliorate cardiac dysfunction in patients with advanced HF. In this review, we focus on the recent advances in cell- and gene-based therapies in the context of cardiovascular disease, emphasizing the most advanced therapies. The principles and mechanisms of action of gene and cell therapies for HF are discussed along with the limitations of current approaches. Finally, we highlight the emerging technologies that hold promise to revolutionize the biological therapies for cardiovascular diseases.